Особливості початку досудового розслідування домашнього насильства (ст. 126-1 КК України) - Абламський, С. Є.; Ablamskyi, S. Ye.; Лук’яненко, Ю. В.; Lukianenko, Yu. V.; Абламський Сергій Євгенович (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 234-249, 2022)
Досліджено законодавство щодо протидії та запобігання домашньому насильству. Проаналізовано судову практику у справах про домашнє насильство (ст. 126-1 КК України). Визначено особливості початку досудового розслідування кримінальних правопорушень про домашнє насильство (ст. 126-1 КК України).

Prevention, counteraction and investigation of criminal offenses is a priority task of law enforcement agencies for any legal, democratic state. While the general issues of combating domestic violence are being studied at the scientific level for a long time, the specifics of initiating an investigation of this destructive phenomenon have remained understudied, which indicates the relevance of the topic for scientific discussion. This aspect has also an important practical significance, as it is shown in the analysis of the studied case law. It has been identified and analyzed the peculiarities of initiating a pre-trial investigation on domestic violence, in particular: firstly, domestic violence (Article 126-1 of the Criminal Code of Ukraine) is classified as a criminal proceeding carried out in the form of private prosecution, and therefore it is initiated at the request of the victim; secondly, when an investigator, interrogator or prosecutor enters information about a criminal offense into the Unified Register of Pre-trial Investigations under Article 126-1 of the Criminal Code of Ukraine, there must be information about repeated (three or more times) bringing the offender to administrative responsibility under Article 173-2 of the Code of Ukraine on Administrative Offenses or about committing systematic actions related to domestic violence. In this regard, it should be noted that bringing a person to administrative liability is only one way of providing evidence. If a person has not been brought to administrative responsibility, but has systematically committed acts (domestic violence), then it is reasonable to consider criminal liability for the relevant actions. It has been determined that difficulties arise due to the fact that, on the one hand, the investigator, interrogator or prosecutor must have information about the intentional systematic commission of domestic violence by a person, and on the other hand, the commission of such an act against a spouse or former spouse or other person with whom the perpetrator is (was) in a family or close relationship.

Исследовано законодательство по противодействию и предотвращению домашнего насилия. Проанализирована судебная практика по делам о домашнем насилии (ст. 126-1 УК Украины). Определены особенности начала досудебного расследования уголовных правонарушений о домашнем насилии (ст. 126-1 УК Украины).
Peculiarities of initiating a pretrial investigation on domestic violence (Article 126-1 of the Criminal Code of Ukraine)
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Кримінологія. Criminology. Криминология; насильство; домашнє насильство; domestic violence; домашнее насилие; початок досудового розслідування; beginning of the pre-trial investigation; начало досудебного расследования; відповідальність; responsibility; ответственность; протидія домашньому насильству; combating domestic violence; противодействие домашнему насилию